PERAN GURU DALAM MENINGKATKAN MINAT BACA SISWA KELAS IV DI MI NU JATIREJOYOSO - yan Rahmawati; Ifa nurhayati (Universitas Islam Raden Rahmat Malang, 2023)
One of the tasks of an educator is to coordinate students in learning activities, within the scope of education, reading is an important skill for students to learn. This research focuses on the urgency of educators who are required to have a contribution in increasing interest in reading in individual students. The fact that interest in reading is low among students then becomes the reason for this research being carried out. A fact, where growing, caring for and accommodating students' interest in reading is the role of a teacher. Reflecting on field conditions, this research then uses a qualitative model that is collaborated with a descriptive approach. For the understanding of the descriptive approach, it can be interpreted as research based on a specified group, one situation, one form of idea, or one class of events. While the expected goals of qualitative research with a descriptive approach are oriented towards accurate writing which includes the preparation of sketches in a structured, valid, and on target manner related to events that are of temporary concern. The research results show that the teacher's role is as a teacher, inspirer, initiator, motivator, facilitator, class manager, mediator, and evaluator. Then for supporting conditions in the implementation of increasing students' interest in reading, between academic aspects, environment, infrastructure and learning materials. The inhibiting factors are academic, environmental, and infrastructure that are not used as well as possible, such as the internet network. Characteristics of grade 4 students, who like picture books.